The relationship between self-efficacy, awareness and subjective norms with online shopping self-protection practices among Chinese consumers in Seremban, Negeri Sembilan - Tham, Jing Yi; Muhammad Arif, Afida Mastura (Malaysia Consumer and Family Economy Association, 2021)
This research seeks to identify the relationship between self-efficacy, awareness and subjective norms with online shopping self-protection practices among the Chinese consumers in Seremban, Negeri Sembilan. There were 200 Chinese respondents from Seremban who participated in this research through the systematic sampling method. Data were collected through a self-administrative survey questionnaire. A five-point Likert scale was used to measure the independent variables and dependent variables of this research. The findings revealed a positive and significant relationship between consumer awareness (r=0.468, p=0.000), subjective norm (r=0.192; p=0.007) and online shopping self-protection practices. However, consumer self-efficacy did not have a significant relationship with online shopping self-protection practices. In order to enhance awareness and subjective norms among consumers, the consumer associations and government agencies may organize more online shopping self-protection programs such as awareness campaigns for the consumers. As online shopping has become a new norm of acquiring goods and services, future research may explore more possible factors contributing to online shopping self-protection practices among consumers.